Survival of Northern Bobwhite Infected with Avian Pox - Brad S. Mueller; William R. Davidson; James B. Atkinson Jr. (National Quail Symposium Proceedings, 2017)
Avian pox is an enzootic disease among northern bobwhite (Colinus virginianus) in the southeastern United States, but occasionally it occurs as local or regional epizootics. Little information exists concerning survival of wild bobwhite infected with this disease. During the winters of 1985 and 1986, we compared survival of radio-tagged bobwhite with and without pox lesions. Pox lesions were considered "wet" or "dry" depending on field evaluations. The incidence of pox was greater in 1985 (x1=' 16.536, df= 1, P< 0.005) than in 1986. Bobwhite with wet pox lesions weighed less than those with dry pox (t = 2.550, P = 0.014) or no pox (t = 2.393, P = 0.018). In 1985 6-week survivorship of bobwhite showing signs of wet pox was different compared to those with dry pox (Z = 1. 7 498, P = 0.0402) and no pox (Z = 2.9992, P = 0.0014). Survivorship of birds with dry pox and no pox was not different (Z = 0.6460, P = 0.2611. Bobwhite with wet pox in 1985 had 45.6 and 53.3% overall lower 6-week survival rates than birds with dry and no pox, respectively. No difference in survivorship existed between bobwhite with dry pox and those with no pox in 1986 (Z = 1.1727, P= 0.1210). No difference in predatory agents responsible for mortalities between birds with or without pox occurred (X2 = 0.8851, df= 2, P> 0.05). All mortality of infected birds appeared to be caused by predation and not the disease itself. Implications of these data for inter- and intraspecific disease transmission are discussed.
Keywords: avian pox; Colinus virginianus; mortality; northern bobwhite; radio-tagging